Pelatihan Pembuatan Bar Soap di SMP Nahdlatul Ulama Medan - Harahap, Siti Nurlani; Sari, Dini Novita; Sari, Fitri Dian Nila; Utami , Khairuna; Ritonga, Nurul Ajima; Lubis, Ruhilah; Sukapiring, Dewi Novina (Universitas Nahdlatul Ulama Sumatera Utara, 2025)
This activity aims to provide education to students about the benefits and how to make bar soap; introduce the tools and materials used to make bar soap. This activity was carried out at Nahdlatul Ulama (NU) Medan Middle School. The method for implementing community service consists of 3 stages, namely the preparation stage, the implementation stage and the reporting stage. In the preparation stage, preparations are made for socialization, determining the location of Community Service, coordinating with the school principal, as well as preparing proposals and completing supporting documents. At the implementation stage, a pre-test was given to students on how to make bar soap. The socialization was carried out by the presenter. After the socialization was completed, a post-test was conducted on the soap, games were played, group photos were taken, and the soap that had been prepared was distributed. At the reporting stage, namely the preparation of documents in the form of activity results reports. The results of this activity have had a significant impact on increasing students' understanding, which can be seen from the pre-test and post-test data that have been carried out. Before the PKM activity was carried out, only 11% of participants knew that cooking oil could be used for other purposes besides frying. Only 9% of participants knew that cooking oil could be processed into soap, only 6% of participants knew the ingredients used to make soap, and only 14% of participants knew the process of making soap. After the PKM activity, 100% of participants knew that cooking oil could be used as a basic ingredient for making soap, 89% of participants knew that cooking oil could be processed into soap, 77% of participants knew the ingredients used in making soap, and 86% of participants knew the process of making soap.